Float - Carson, Anne, 1950- (Alfred A. Knopf, 2016)
"Anne Carson consistently dazzles with her inventive, shape-shifting work and the vividness of her imagination. Float reaches an even greater level of brilliance and surprise. Presented in an arrestingly original format--individual chapbooks that can be read in any order, and that float inside a transparent case--this collection conjures a mix of voices, time periods, and structures to explore what makes people, memories, and stories "maddeningly attractive" when observed in spaces that are suggestively in-between. One can begin with Carson contemplating Proust on a frozen Icelandic plain, or on the art-saturated streets of downtown New York City. Or journey to the peak of Mount Olympus, where Zeus ponders his own afterlife. Or find a chorus of Gertrude Steins performing an essay about falling--a piece that also unearths poignant memories of Carson's own father and great-uncle in rural Canada. And a poem called "Wildly Constant" piercingly explores the highs and lows of marriage and monogamy, distilled in a wife's waking up her husband from the darkness of night, and asking him to make them eggs for breakfast."--